The Influence of Accountability and Transparency of Government Financial Reports on The Achievement of Sustainable Development Goals (SDGS 11) in Indonesia - Astrid Astrid; Muhammad Iqbal; Femilia Zahra; Rudy Usman (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the influence of accountability and transparency in local government financial reports on the achievement of Sustainable Development Goals (SDGs) 11, specifically the indicator of access to decent and affordable housing in Indonesia. The study used panel data from 31 provinces during the 2021–2024 period with a total of 124 observations. The research data were obtained from the Central Statistics Agency (BPS), the Supreme Audit Agency (BPK), and official local government websites related to the publication of financial reports. Data analysis was conducted using the Generalized Least Squares (GLS) method with a Random Effect Model (REM) approach. The results of the study indicate that accountability has a positive and significant effect on the achievement of SDG 11. These findings indicate that accountable regional financial management can increase the effectiveness of housing and settlement development programs. Transparency also has a positive and significant effect on the achievement of SDG 11, with a stronger effect than accountability. Openness of financial information encourages public oversight of regional budget use and increases the efficiency of development program implementation. The results of simultaneous testing indicate that accountability and transparency together have a significant effect on the achievement of the indicator of access to decent and affordable housing. The research findings support the theory of good governance, which places accountability and transparency as essential elements in improving the quality of local government governance. This study provides an empirical contribution regarding the relationship between local government financial governance and the achievement of sustainable settlement development in Indonesia.